2008
DOI: 10.1002/syn.20582
|View full text |Cite
|
Sign up to set email alerts
|

Racemic gamma vinyl‐GABA (R,S‐GVG) blocks methamphetamine‐triggered reinstatement of conditioned place preference

Abstract: Preventing relapse poses a significant challenge to the successful management of methamphetamine (METH) dependence. Although no effective medication currently exists for its treatment, racemic gamma vinyl-GABA (R,S-GVG, vigabatrin) shows enormous potential as it blocks both the neurochemical and behavioral effects of a variety of drugs, including METH, heroin, morphine, ethanol, nicotine, and cocaine. Using the reinstatement of a conditioned place preference (CPP) as an animal model of relapse, the present stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
11
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 70 publications
6
11
0
Order By: Relevance
“…These findings are in general agreement with several studies by Ribeiro and co-workers, in which physical (restraint and tail pinch) and social defeat stressors induced reinstatement of drug-induced CPP (Ribeiro Do Couto et al 2009;Ribeiro Do Couto et al 2006). The current results are also in agreement with a different study in which stress in rats reinstates alcohol selfadministration ) and with the findings that a priming injection of ethanol, cocaine, amphetamine, and morphine reinstate drug CPP (DeMarco et al 2009;Feng et al 2011;Font et al 2008;Romieu et al 2004). …”
Section: Discussionsupporting
confidence: 92%
“…These findings are in general agreement with several studies by Ribeiro and co-workers, in which physical (restraint and tail pinch) and social defeat stressors induced reinstatement of drug-induced CPP (Ribeiro Do Couto et al 2009;Ribeiro Do Couto et al 2006). The current results are also in agreement with a different study in which stress in rats reinstates alcohol selfadministration ) and with the findings that a priming injection of ethanol, cocaine, amphetamine, and morphine reinstate drug CPP (DeMarco et al 2009;Feng et al 2011;Font et al 2008;Romieu et al 2004). …”
Section: Discussionsupporting
confidence: 92%
“…The first experiment revealed that the current conditioning procedure produced significant METH CPP at all tested doses and that the CPP was extinguished by exposing rats to the previously drug-paired chamber for 4 sessions in the absence of METH. It is possible that the dose-dependent nature of METH CPP requires a longer period of training [17]; however, the findings of the current study are consistent with those observed by DeMarco et al [16] in which dose-dependency was not observed following 10 METH pairings. It should be noted that SAL was administered prior to each test session in the current set of experiments (i.e.…”
Section: Discussionsupporting
confidence: 91%
“…On this pre-conditioning test day, rats were administered SAL immediately before being placed into the neutral chamber and had access to all three chambers. The time spent in each chamber during this 15 min test was assessed and any animal which spent ≥80% of the total test time [after 15, 16] in either end chamber was considered to have an initial bias for one chamber and was excluded from further testing. On days 3–10, rats were randomly assigned to treatment groups and underwent conditioning sessions in a counterbalanced, unbiased fashion (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…Another important consideration that percolated through these experiments was the extent to which the imaging measurements influenced animal behavior. The preference produced by METH in these studies was comparable to other studies from our laboratory which did not involve imaging (DeMarco et al 2008), where in both cases roughly 25% of the animals did not show a preference after conditioning. However, there are several components of the imaging that may influence the behavior under investigation.…”
Section: Discussionsupporting
confidence: 87%